IMPLEMENTASI PENGGUNAAN GOOGLE CLASSROOM PADA PEMBELAJARAN IPA DI SDN 105366 SEI NAGALAWAN - Holmes Parhusip; Irwansyah Irwansyah; Hartono Sembiring; Heryanto Heryanto (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2021)
This research is motivated because schools during the Covid -19 pandemic are required to use virtual teaching methods or teleconferencing so that the SDN 105366 Sei Nagalawan school uses teaching methods using Google Claasroom and it is important for teacher researchers and students to find out how the results of implementing the virtual teaching method are. The method in this study uses observation, interviews and documentation. This study also aims to determine the learning outcomes of students who are taught using Google Classroom and compare the learning outcomes taught by conventional methods with those taught using Google Class Room. Based on the data from the research that has been carried out, it can be concluded that the implementation of the use of Google Classroom is very helpful in the online learning process during the current Covid-19 pandemic, while using the Google Classroom application the teacher can monitor student learning activities, such as absenteeism, material explanations. and delivery of assigned tasks, and the teacher also prepares learning videos.